Analysis on convective heat transfer coefficients of external surfaces for typical building arrays. (15th December 2022) - Zheng, Shu; Wang, Yi; Feng, Fan; Xue, Yu; Wang, Zhichao; Duanmu, Lin
Abstract: Urban architecture has a great impact on the flow field among buildings, leading to the varying of building surface convective heat transfer coefficient (CHTC), which then influences heat exchange and heating/cooling energy consumption. This paper proposes a method to correct CHTC with a shelter factor by analyzing the effect of mutual shielding among buildings. The characteristic data of 51 green energy-saving residential buildings in China are collected, then classifies with the K-means method to get typical building arrays. CFD simulations are used to compare the CHTC ratios of buildings in a typical building array with those of individual buildings at different wind speeds. The shelter factor of CHTC in building arrays is obtained. The CHTC of buildings in different arrays is 24%–77% of a single building. Different types of building arrays show different CHTC characteristics. The energy consumption of a building among building arrays, calculated with corrected CHTC, is further compared with the value of a single building. The results show that the greater the building wall heat transfer coefficient is, the greater the influence of the shelter factor on building energy consumption. Highlights: This paper presents a method for determining typical building arrays in urban. The spatial distribution characteristics of CHTC of typical building arrays are analyzed. The shelter factor in typical building arrays is obtained to correct the CHTC value of buildings in the urban. The sensitivity of annual energy consumption to CHTC modifications is investigated.